2019
DOI: 10.3906/sag-1901-193
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of cyclosporine A in the treatment of severe hydronephrosis in a rabbit renal pelvic perfusion model

Abstract: Introduction With the development of minimally invasive technology, many types of ureteroscopy and percutaneous nephroscope lithotripsy have become routine procedures in surgical intervention for kidney stones, as they have several advantages, including reduced postsurgical pain, efficient stone clearance, shorter hospitalization time, and reduced scar formation than open surgery [1,2]. However, minimally invasive surgery in the kidney may not be minimally invasive within the kidney itself. Endourological oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…IL-6 acts directly on cardiomyocytes to induce myocardial inhibition by altering the function of the sarcoplasmic reticulum and reducing the concentration of calcium ions in the cell cytoplasm (44). IL-6 has also been previously revealed to serve an important regulatory role in myocardial apoptosis in a rat model of MIRI (35). Therefore, the anti-inflammatory and anti-apoptotic effects of Gal-1 significantly alleviated MIRI in rats in the current study.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…IL-6 acts directly on cardiomyocytes to induce myocardial inhibition by altering the function of the sarcoplasmic reticulum and reducing the concentration of calcium ions in the cell cytoplasm (44). IL-6 has also been previously revealed to serve an important regulatory role in myocardial apoptosis in a rat model of MIRI (35). Therefore, the anti-inflammatory and anti-apoptotic effects of Gal-1 significantly alleviated MIRI in rats in the current study.…”
Section: Discussionsupporting
confidence: 53%
“…Other studies using MIRI rabbit models confirmed that apoptosis did not occur after reperfusion for 4 h following myocardial ischemia for 5 min (33,34). Additionally, no myocardial apoptosis was detected after 30 min of ischemia (35). However, after ischemia for 30 min and reperfusion for 4 h, cardiomyocytes exhibited marked apoptosis, suggesting that cardiomyocyte apoptosis is not only dependent on reperfusion injury, but also on the length of ischemia.…”
Section: Discussionmentioning
confidence: 87%